Malay Medicinal Practices and Prophetic Foods for Treating the Four Types of Illnesses Most Commonly Found in the Bottom Billion Population of the World: A Systematic Review of Malay Manuscripts Found in Malaysia - Nasir, MN; Nasir, MA; Sempo, MW; Sahid, MM; Razif, AM; Rahman, TSA; Lockman, H; Anuar, K; Rani, MDM; Syaiful, A; Ithnin, M; Aripin, KNB (American Scientific Publishers, 2024)
Indexed by WOS/SCOPUS